ANALISIS LATIHAN KETERAMPILAN MENULIS PADA BUKU AJAR â€œDEUTSCH IST EINFACH 1â€ UNTUK SISWA KELAS X SMA - KURNIA K, RIBKA (LATERNE, 2016)
The process of learning a foreign language, requires a source to inform one of them a textbook. Foreign language textbooks has four language skills to achieve learning objectives. Under these conditions must, as educators, to get acquainted with the practice, the suitability of the learning objectives. Textbook